2019
DOI: 10.1001/jamanetworkopen.2019.10154
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hormone Therapy and Muscle Mass in Postmenopausal Women

Abstract: Key Points Question In postmenopausal women 50 years or older, is estrogen-based hormone therapy associated with reduced loss of lean body mass compared with no hormone therapy? Findings In this systematic review and meta-analysis of 12 studies comprising 4474 postmenopausal women, those who received estrogen-based hormone therapy lost less lean body mass compared with women who received no hormone therapy and women who received placebo, but this finding wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 70 publications
0
46
0
2
Order By: Relevance
“…Because the between‐group differences in changes in FFM were not statistically significant, the effect of the exercise intervention must be interpreted cautiously and should be confirmed. Interestingly, a recent systemic review and meta‐analysis found no beneficial effect of hormone therapy on muscle mass retention in postmenopausal women (38). This emphasizes the need to more thoroughly understand the role of estrogen in maintenance of FFM in women and to develop strategies for preventing loss in aging women.…”
Section: Discussionmentioning
confidence: 99%
“…Because the between‐group differences in changes in FFM were not statistically significant, the effect of the exercise intervention must be interpreted cautiously and should be confirmed. Interestingly, a recent systemic review and meta‐analysis found no beneficial effect of hormone therapy on muscle mass retention in postmenopausal women (38). This emphasizes the need to more thoroughly understand the role of estrogen in maintenance of FFM in women and to develop strategies for preventing loss in aging women.…”
Section: Discussionmentioning
confidence: 99%
“…The potential contribution of CSA/periodic breathing on decline in heart function and outcomes motivated clinicians and researchers to delineate optimal treatment strategies. Therapeutic goals include improvement in cardiac function, reduction of hospitalisations, morbidity and mortality and, if these are not possible, enhancement of quality of life (QoL) [22].…”
Section: Challenges In Managing Csa/periodic Breathing In Chf With Rementioning
confidence: 99%
“…However, the study results have been challenged owing to a high percentage (23%) of the study population switching from control to ASV or vice versa, low ASV adherence (40% of patients used the ASV device <3 h per day, 26.7% 0 h per day) and unbalanced use of antiarrhythmic drugs between the two arms [45,46]. Post hoc analyses showed that ASV negative impact was mainly restricted to patients with the lowest LVEF (<30%) and those with the highest proportion of periodic breathing [22,47]. Therefore, the contraindications of ASV should not been extended to the CHF population with preserved ejection fraction and/or to HFrEF >45%.…”
Section: Challenges In Managing Csa/periodic Breathing In Chf With Rementioning
confidence: 99%
“…However, several limitations, such as the inclusion of studies with low-quality evidence, lack of information on the impact of different regimens (i.e., cyclical vs. continuous HRT, amount of physical activity, and ethnicity), need to be acknowledged. 101 Conversely, a more recent study of 4,254 Korean women showed that prolonged use of HRT was associated with higher muscle mass and lower prevalence of sarcopenia in postmenopausal women with more pronounced effects in younger and leaner women. 102 However, data examining the effect of estrogen replacement on muscle endpoints in POI is scarce, with one study in adult women with TS showing an increase in LBM with higher doses of oestradiol.…”
Section: Estrogen Replacement and Other Hormonal Therapiesmentioning
confidence: 96%